2017
DOI: 10.1113/jp273046
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule mechanics in the working myocyte

Abstract: The mechanical role of cardiac microtubules (MTs) has been a topic of some controversy. Early studies, which relied largely on pharmacological interventions that altered the MT cytoskeleton as a whole, presented no consistent role. Recent advances in the ability to observe and manipulate specific properties of the cytoskeleton have strengthened our understanding. Direct observation of MTs in working myocytes suggests a spring-like function, one that is surprisingly tunable by post-translational modification (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
(54 reference statements)
1
24
0
Order By: Relevance
“…Control cardiac myocytes (Fig. 1A, left) displayed a sparse, complex network of microtubules, similar to previous reports (Robison and Prosser, 2017). In contrast, cardiac myocytes treated with 100 μM H 2 O 2 (Fig.…”
Section: Oxidative Stress Increases Longitudinal Alignment Of the Micsupporting
confidence: 88%
“…Control cardiac myocytes (Fig. 1A, left) displayed a sparse, complex network of microtubules, similar to previous reports (Robison and Prosser, 2017). In contrast, cardiac myocytes treated with 100 μM H 2 O 2 (Fig.…”
Section: Oxidative Stress Increases Longitudinal Alignment Of the Micsupporting
confidence: 88%
“…Although poorly understood in fish, the steps of myogenesis in mouse models provide clues, including commitment of muscle precursors, myoblast proliferation, migration, alignment, and fusion into myotubes (Buckingham and Rigby, 2014). Myocytes are mainly filled with myofibrils, which are long protein cords composed of myofilaments comprising molecules called myosin, actin, or titin (Sanger et al, 2016;Robison and Prosser, 2017). The relative contribution of hyperplasia and hypertrophy to muscle growth is known to be regulated by many nutritional factors, among which, proteins play a major role, given the importance of protein deposition on muscle growth (Alami-Durante et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Together, the polymerized form of α-tubulin and β-tubulin assembles the microtubule network, which supports the architecture, contractile function and transportation of cytoplasmic constitutes within the cardiomyocyte [31][32][33]. Previously, we showed that tachypacing induces disruption of the microtubule network via activation of HDAC6, resulting in deacetylation, depolymerization and finally degradation of the depolymerized α-tubulin by calpain.…”
Section: Gga*-59 Post-treatment Restores α-Tubulin Networkmentioning
confidence: 57%